Implicit Bias about Disabilities: Does it Exist for Forensic Interviewers and Could It Affect Child Credibility Decisions in Child Abuse Investigations: An Exploratory Study - Reiman, Elizabeth (2014)
This research project considered two questions regarding forensic interviewers: Do forensic interviewers hold implicit biases toward people with disabilities? If so, could this influence whether a forensic interviewer finds a child with a disability believable? To examine these questions, a quantitative exploratory study was conducted. Using an online survey, participants were randomly assigned to read a scenario about a child's disclosure of sexual abuse (children with and without a disability), and respond to questions about the believability of the child. Participants then completed an adapted version of the Disability Attitude Implicit Association Test (DA-IAT). The results yielded four significant findings. First, implicit bias about disabilities does exist in the forensic interviewer population. The results suggest that bias about disabilities exists on a continuum (High Bias, Low Bias and No Bias) and not in a binary representation as previously measured by other authors. Second, of all the interviewer characteristics that might predict representation in the three bias groups, only professional discipline was significant. The third conclusion demonstrated that, the interviewer attributes showed a significant relationship to credibility but none of the child characteristics were associated. The fourth finding was that the identification of a disability prior to the interview could affect the interviewer's bias score. The results raise the question of how interviewer's implicit bias about disabilities can change the course of an interview. Using this information as a starting point, further research on this topic is critical to forensic interview best practice. The training of these specialized practitioners needs to move beyond simply providing basic information about disabilities and begin to explore interviewers' beliefs, attitudes and values about people with disabilities